2009
DOI: 10.1158/0008-5472.can-08-3490
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Transcription Factor-1 Inhibits Transforming Growth Factor-β–Mediated Epithelial-to-Mesenchymal Transition in Lung Adenocarcinoma Cells

Abstract: Thyroid transcription factor-1 (TTF-1) is expressed in lung cancer, but its functional roles remain unexplored. TTF-1 gene amplification has been discovered in a part of lung adenocarcinomas, and its action as a lineage-specific oncogene is highlighted. Epithelial-to-mesenchymal transition (EMT) is a crucial event for cancer cells to acquire invasive and metastatic phenotypes and can be elicited by transforming growth factor-B (TGF-B). Mesenchymal-to-epithelial transition (MET) is the inverse process of EMT; h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 32 publications
5
107
0
Order By: Relevance
“…Thus, we tested the contribution of SIP1 to A771726-induced EMT-like phenotypes using its siRNA (unfortunately, we could not obtain siRNA that efficiently suppresses the It has also been reported that TGF-b 1 upregulates the expression of EMT-related transcription factors, including SIP1. 23,24 However, as shown in Supplementary Figure S2a Next, we tested the contribution of the Notch-signaling pathway to A771726-induced EMT-like phenotypes. This pathway, which is triggered by the binding between Notch receptors (Notch-1-4) and ligands (such as Jagged-1, 2 and Delta-like 1 (Dll-1)), is mediated by two proteolytic cleavage events involving the Notch receptor.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we tested the contribution of SIP1 to A771726-induced EMT-like phenotypes using its siRNA (unfortunately, we could not obtain siRNA that efficiently suppresses the It has also been reported that TGF-b 1 upregulates the expression of EMT-related transcription factors, including SIP1. 23,24 However, as shown in Supplementary Figure S2a Next, we tested the contribution of the Notch-signaling pathway to A771726-induced EMT-like phenotypes. This pathway, which is triggered by the binding between Notch receptors (Notch-1-4) and ligands (such as Jagged-1, 2 and Delta-like 1 (Dll-1)), is mediated by two proteolytic cleavage events involving the Notch receptor.…”
Section: Resultsmentioning
confidence: 99%
“…We believe that there is a significant crosstalk between the transcriptional program and miRNA network in the lung (diseased or normal), and miR-365 is merely "a tip of an iceberg." In the intriguing signaling loop reported by Saito et al, TGFβ induced TTF-1 downregulation, thus blunting the anti-EMT activity associated with TTF-1, 27 but the molecules mediating this activity were unidentified. In this study, we present evidence that miR-365 mediates TTF-1 repression by TGFβ.…”
Section: Discussionmentioning
confidence: 97%
“…Saito et al recently reported that TTF-1 inhibits TGFβ-mediated EMT in lung cancer cells, 27 suggesting that TTF-1 is an anti-EMT factor. In their study, TGFβ treatment led to downregulation of TTF-1, blunting the anti-EMT phenotype conferred by the TTF-1 protein.…”
Section: S6)mentioning
confidence: 99%
See 2 more Smart Citations